Marsupials (Didelphidae, Mammalia) of Mato Grosso do Sul state (Brazil): taxonomic accounts, species richness, and biogeography - Nilton C. Cáceres; Geruza L. Melo; Jonas Sponchiado; Gabriel M. Martin (ZooKeys, 2025)
The marsupials of Mato Grosso do Sul (MS) state in southwestern Brazil are still poorly known, with most research being concentrated around the Pantanal wetland. In this work, the marsupial richness was analysed in four different ecoregions of MS, based on more than ten years of sampling using live and pitfall traps, comparing them with published information. Fifteen marsupial species were recorded, adding 117 new records and increasing the previously known richness by more than 50%. These new records represent an increase between 96.7% (Gracilinanus agilis) to 9.1% (Chironectes minimus) of those previously known for the state, with an average increase of 43%. Cryptonanus agricolai is recorded for the first time for MS, but we did not trap Caluromys lanatus and Metachirus myosuros, which were mentioned in the literature. The Cerrado ecoregion (a type of savanna) shows more species than other ecoregions, being the largest ecoregion in the state. A strong faunal turnover was found in the state, from the humid and mild forests of the southeast (Atlantic forest ecoregion) to the more seasonal, dry, and warm forests, shrublands, and grasslands of the northwest (Chiquitano and Pantanal ecoregions). A full taxonomic account and localities of the species recorded are provided and the biogeographical affinities of ecoregions present in MS are discussed.